Russia's agri-food trade with the Middle East and North Africa - Maximilian Heigermoser; Tinoush Jamali Jaghdani; Linde Götz (Russia's role in the contemporary international agri-food trade system, 2022)
The Middle East and North Africa (MENA) region is the top destination for Russian food exports, grains in particular. Focusing on Turkey, Egypt, Iran, and Saudi Arabia, this chapter shows that Russia's food trade with MENA countries is strongly affected by bilateral political relations. Russia banned most food imports from Turkey over a political conflict in 2016. In the same year, improved intergovernmental cooperation with Saudi Arabia resulted in a diversification of Russia's food exports to the Gulf country, and in 2019, Iran's accession to the Eurasian Economic Union (EAEU) led to increasing food trade with Russia. Food imports in MENA countries are usually managed by powerful state trading enterprises (STEs), which recurrently disapprove food products originating from Russia based on non-adherence to food quality standards. Our analysis shows that Russia is successfully working to open additional destination markets, while simultaneously impeding imports of food products that it aims to produce domestically.
Keywords: 630; Black Sea exporters; grain markets; trade policy; Russia; Middle East and North Africa; non-tariff barriers